2015
DOI: 10.1162/jocn_a_00862
|View full text |Cite
|
Sign up to set email alerts
|

Musical Meter Modulates the Allocation of Attention across Time

Abstract: Dynamic Attending Theory predicts that attention is allocated hierarchically across time during processing of hierarchical rhythmic structures such as musical meter. Event-related potential (ERP) research demonstrates that attention to a moment in time modulates early auditory processing as evidenced by the amplitude of the first negative peak (N1) approximately 100 ms after sound onset. ERPs elicited by tones presented at times of high and low metric strength in short melodies were compared to test the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 74 publications
15
37
1
Order By: Relevance
“…Temporal expectations have been reported to both enhance and attenuate the auditory P1 and N1 responses. Enhancement of sensory responses at expected time points (Bouwer & Honing, 2015;Escoffier et al, 2015;Fitzroy & Sanders, 2015;Hsu, Hämäläinen, & Waszak, 2013;Rimmele, Jolsvai, & Sussman, 2011;Tierney & Kraus, 2013) is in line with entrainment models of temporal expectations, which assume increased sensory gain at expected time points (Large & Jones, 1999). By contrast, attenuation of sensory responses at expected time points (Lange, 2009;Paris, Kim, & David, 2016;Sanabria & Correa, 2013;Sherwell, Garrido, & Cunnington, 2017;van Atteveldt et al, 2015) is in line with predictive models of brain function that assert more efficient processing of incoming information when predicted information is suppressed (Friston, 2005;Marzecová, Widmann, Sanmiguel, Kotz, & Schröger, 2017;Schröger, Kotz, & SanMiguel, 2015;Schröger, Marzecová, & Sanmiguel, 2015).…”
supporting
confidence: 68%
“…Temporal expectations have been reported to both enhance and attenuate the auditory P1 and N1 responses. Enhancement of sensory responses at expected time points (Bouwer & Honing, 2015;Escoffier et al, 2015;Fitzroy & Sanders, 2015;Hsu, Hämäläinen, & Waszak, 2013;Rimmele, Jolsvai, & Sussman, 2011;Tierney & Kraus, 2013) is in line with entrainment models of temporal expectations, which assume increased sensory gain at expected time points (Large & Jones, 1999). By contrast, attenuation of sensory responses at expected time points (Lange, 2009;Paris, Kim, & David, 2016;Sanabria & Correa, 2013;Sherwell, Garrido, & Cunnington, 2017;van Atteveldt et al, 2015) is in line with predictive models of brain function that assert more efficient processing of incoming information when predicted information is suppressed (Friston, 2005;Marzecová, Widmann, Sanmiguel, Kotz, & Schröger, 2017;Schröger, Kotz, & SanMiguel, 2015;Schröger, Marzecová, & Sanmiguel, 2015).…”
supporting
confidence: 68%
“…However, Schafer et al (1981) found a larger P2 potential in the condition where no temporal information was available compared to when a tone appeared in synchrony with the beat. Recently, Fitzroy and Sanders (2015) found a larger P2 for auditory tones which appeared at a weak (unattended) compared to strong (attended) metric beat with a similar time interval (150-190 ms) and posterior topography of the effect (although this was the case in a musicians group only; in a non-musician group the effect was reversed). The present study confirms these latter results.…”
Section: Discussionmentioning
confidence: 96%
“…It may be the case that the regular metric structure of these texts helps listeners attend better to the content they hear. Specifically, regular metric patterns allow listeners to make predictions about when in time upcoming information is going to occur (Huron, 2006;Fitzroy & Sanders, 2015). Moreover, adult listeners have been shown to exploit regular metric patterns as cues to speech segmentation (Mattys & Samuel, 1997), lexical organization (Breen, Dilley, McAuley, & Sanders, 2014), syntactic structure (Schmidt-Kassow & Kotz, 2009), and semantic structure (Rothermich, Schmidt-Kassow, & Kotz, 2012).…”
Section: Discussionmentioning
confidence: 99%